hERG1 Channels and Glut-1 as Independent Prognostic Indicators of Worse Outcome in Stage I and II Colorectal Cancer: A Pilot Study - Lastraioli, Elena (Neoplasia Press Inc., 2012)
BACKGROUND: There is a need to identify new markers to assess recurrence risk in early-stage colorectal cancer (CRC) patients. We explored the prognostic impact of ether-a-gò-gò-related gene 1 channels and some hypoxia markers, in patients with nonmetastatic (stage I, II, and III) CRC. METHODS: The expression of hERG1, vascular endothelial growth factor A (VEGF-A), glucose transporter 1, carbonic anhydrase IX (CA-IX), epidermal growth factor receptor (EGF-R), and p53 was tested by immunohistochemistry in 135 patients. The median follow-up was 35 months. Clinicopathologic parameters and overall survival were evaluated. RESULTS: hERG1 displayed a statistically significant association with Glut-1, VEGF-A, CA-IX, and EGF-R; p53 with VEGF-A and CA-IX; Glut-1 with the age of the patients; and EGF-R with TNM and mucin content. TNM and CA-IX were prognostic factors at the univariate analysis; TNM, hERG1, and Glut-1, at the multivariate analysis. Risk scores calculated from the final multivariate model allowed to stratify patients into four different risk groups: A) stage I–II, Glut-1 positivity, any hERG1; B) stage I–II, Glut-1 and hERG1 negativity; C) stage I–II, Glut-1 negativity, hERG1 positivity; D) stage III, any Glut-1 and any hERG1. CONCLUSIONS: hERG1 positivity with Glut-1 negativity identifies a patient group with poor prognosis within stage I–II CRC. The possibility that these patients might benefit from adjuvant therapy, independently from the TNM stage, is discussed. IMPACT: More robust prognostic and predictive markers, supplementing standard clinical and pathologic staging, are needed for node-negative patients.